Attempts to Preserve Zadrugas in Practice of Serbian Court of Cassation - Kulauzov, Maša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
Decisions of Serbian Court of Cassation regarding preserving so – called zadrugas (extended families, common among South Slavs) are subject of this paper. Although market economy and prevailing private property are in sharp contrast to nontransferable estate and collective character of zadruga᾽s ownership, yet in second half of 19th century patriarchal families had many advocates. Therefore, verdicts passed with aim to stop divisions of zadrugas and fragmentation of zadruga᾽s property are scrutinized and critically analyzed. Namely, after enaction of Serbian Civil Code in 1844 divisions of zadrugas became increasingly common. Separation of traditional rural families had destructive impact on material status of former zadruga᾽s members, such as excessive indebting and, as a result of overindebtedness, rapid pauperization and impoverishment of villagers. For that reason, many attempts to diminish widespread fragmentation of zadruga᾽s estate and decrease frequency of dissolution of extended families were made in judicial practice. Those measures undertaken in practice of Serbian Court of Cassation are examined in this paper. Author also indicates in which aspects judicial practice regarding preservation of zadrugas was uniform.